Supplementary studies on Anacanthorus penilabiatus and Mymarothecium viatorum (Monogenea: Dactylogyridae) from Piaractus mesopotamicus (Characiformes: Serrasalmidae) in Brazil - Müller, Maria Isabel [UNESP]; Ceccarelli, Paulo Sãrgio; Ueta, Marlene Tiduko (Springer Nature, 2016)
The dactylogyrid monogeneans Anacanthorus penilabiatus (Boeger, Husak and Martins, 1995) and Mymarothecium viatorum(Boeger, Piasecki and Sobecka, 2002), commonly found in large quantities in farmed Piaractus mesopotamicus (Holmberg, 1887) in Brazil, were collected from three fish farms located in the State of São Paulo, Brazil. Morphological and molecular identification, scanning electron microscopy, histopathological and descriptive parameters data were performed. A total of 278 specimens of P. mesopotamicus were gathered from February 2008 and July 2010. Prevalence (P) and mean intensity of infection (MII) data was taken at each location. The data showed prevalence and mean intensity of infection annually, with numbers such as P = 91.2% and MII = 50 worms/fish (Pirassununga), P = 60% and MII = 39.2 worms/fish (Mogi Mirim), and P = 100% and MII = 204.8 worms/fish (Itapira). Histopathological results showed hyperplasia of the secondary lamellae, and hypersecretion of mucus was also observed. A phylogenetic topology was inferred using complete SSU (18S) ribosomal rDNA, positioning Anacanthorus penilabiatus and Mymarothecium viatorum among other monopisthocotyleans available in GenBank.
Keywords: Freshwater fish; monogenean; pacu; ribosomal DNA